A critical analysis of the impact of internal auditing on fraud detection in the cement manufacturing industry of Zimbabwe: impact of internal auditing on fraud detection - Wadesango, Newman; Mutambira, Patience; Sistcha, lovemore; Wadesango, Ongayi (The Journal of Accounting and Management, 2022)
The title of this study was a critical analysis of the impact of internal auditing on fraud detection in the cement manufacturing industry of Zimbabwe. Epistemology was adopted as the philosophical basis of the study and the research paradigm was pragmatism. The quantitative research approach was selected and for data collection, researchers used questionnaires. The convergent parallel research design was used and the target population was made up of 5 000 staff and employees from the three major cement manufacturers in Zimbabwe. The Krejcie and Morgan (1970) table was applied to obtain a research sample of 357. The study made use of simple random sampling and purposive sampling and the data collection instruments used in this study included questionnaires and interviews. The ffindings on the types and extent of use of internal audit in the studied cement manufacturing firms revealed that the mostly used type of internal audits are management audits. The internal audits in the studied firms were found to be poor in most aspects such as the accomplishment of objectives; enhancing organizational effectiveness; preventing errors and other unforeseen problems; risk management and the identification of the basic objective of internal auditing, among others. The effectiveness of the audits is fairly affected by financial, political and legal factors. With regards to the influence of internal audits on the prevention and detection of fraud, findings of the study also suggested that the internal auditing in the studied cement manufacturing firms fails to deal with the major forms of fraud in the organisations, such as skimming payments from customers; check tampering; cash theft; the misuse of company credit cards as well as improper payroll transactions. An R2 of 0.307, with a T value of 0.942 and a significance of 0.446 at the P>0.05 level showed a low but significant relationship between the fraud variable and the internal auditing in the firms. There was also an R2 value of 0.015 and a T value of 0.347 with a significance of 0.738 at the P>0.05 level, showing that there was no significant relationship between the ROA and the performance level of the cement manufacturing firms. Findings on the strategies that could possibly be used to enhance the fraud detection and prevention capabilities of internal audits in the studied firms include undertaking more regular and routine financial auditing and ensuing legal procedures for fraudulent employees who fail to adhere to audit recommendations. The study therefore recommended for the adoption of other internal audit principles and strategies, formulating a consistent internal audit policy, regular financial auditing and to fund the implementation of internal audit recommendations.